Agricultura familiar, pluriatividade e políticas públicas na região nordeste e sul do Brasil, nos anos 1990 e 2000: trajetórias e desafios - Cardoso, Jucyene das Graças (2013)
This thesis aims to contribute to studies around the determinations of pluriactivity and its trajectory over the years 1990 and 2000 in the Northeast and South Regions of Brazil. In this sense, more than inquire about the reasons explaining the existence of pluriactivity in Brazil, this work intends to investigate its growing possibilities inside the northeastern and southerner family farming. It was used in the research data from PNAD/IBGE National Household Sample Survey for the period 1992 to 1999 and 2001 to 2009 and the methodology and typology of families of Rurbano Project (IE/Unicamp). Since the pluriactivity is a concept that describes the reality of the family that plays agricultural occupations (agricultural side of pluriactivity) and non-agricultural occupations (non-agricultural side of pluriactivity), studies point to the fact that there exist explanatory elements of pluriactivity that would be intrinsic and extrinsic to those families. Our working hypothesis is that the intrinsic determinants (those related to internal characteristics of household members, such as family size, age, education) are not enough to explain the behavior of pluriactivity over time. It is understood that the extrinsic determinations (those related to the economic environment, to the conditions of labor market in which families are embedded and to public policies oriented to agriculture) would be more decisive for the growth behavior of pluriativity. Among the extrinsic variables, this thesis considers public policies as the most important for the advancement of pluriactivity over time among families of family farming. It reinforces the importance of the State action through public policies directed to the agricultural side of pluriactivity, especially for the more fragile segment of farmers, for its growth trend. More than an external non-agricultural dynamic environment, it is necessary to expand and create public policies aimed to face the challenges experienced by family farmers in the performance of agricultural activity as a way to promote a trend of increasing the number of pluriactive households inside the Brazilian family farming by minimizing the possibilities of these families turn into non-agricultural households. Play this role policies as the National Program for the Strengthening of Family Farming (PRONAF), the Food Acquisition Programme (PAA) and the National Programme on School Feeding (PNAE), which will be investigated in this study.